1986
DOI: 10.1002/jor.1100040410
|View full text |Cite
|
Sign up to set email alerts
|

Origin of replacement cells for the anterior cruciate ligament autograft

Abstract: A rabbit model for anterior cruciate ligament (ACL) reconstruction using autogenous avascular patellar tendon (PT) was utilized to study the early events of graft incorporation. Histological observations demonstrated that autografts were centrally acellular with a peripheral rim of cells at 2 weeks, a central focal proliferation of cells at 3 weeks, and a cellular homogeneous distribution by 4-weeks postoperation. Graft necrosis followed by cellular proliferation suggested that a different population of cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 22 publications
3
59
0
Order By: Relevance
“…The results of their study are consistent with our findings that cellular necrosis is found in the autogenous patellar tendon graft 1 week after ACL reconstruction and that 2-week old autografts are populated by a peripheral rim of cells with high PCNA-positive rates. The present study also demonstrated that cellular repopulation in the patellar tendon graft is observed 11 before vascular formation in the graft. Kleiner et al [12] also reported that remarkable cellular proliferation occurred in the rabbit patellar tendon graft at 3 weeks after ACL reconstruction, while vascular injection revealed the absence of a blood supply to the graft.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The results of their study are consistent with our findings that cellular necrosis is found in the autogenous patellar tendon graft 1 week after ACL reconstruction and that 2-week old autografts are populated by a peripheral rim of cells with high PCNA-positive rates. The present study also demonstrated that cellular repopulation in the patellar tendon graft is observed 11 before vascular formation in the graft. Kleiner et al [12] also reported that remarkable cellular proliferation occurred in the rabbit patellar tendon graft at 3 weeks after ACL reconstruction, while vascular injection revealed the absence of a blood supply to the graft.…”
Section: Discussionsupporting
confidence: 75%
“…We believe that the findings of the present study provide useful information to clarify the healing process of the patellar tendon graft after ACL reconstruction as discussed below. Kleiner et al [11] showed that the cellular population of the autograft is derived entirely from a source other than the native patellar tendon fibroblasts by graft sequestration experiments. The results of their study are consistent with our findings that cellular necrosis is found in the autogenous patellar tendon graft 1 week after ACL reconstruction and that 2-week old autografts are populated by a peripheral rim of cells with high PCNA-positive rates.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have studied its vascularity (Townley et al, 1985;Amiel et al, 1986a), viability (Amiel et al, 1986b;Nikolaou et al, 1986), biomechanical strength (Whiteside and Sweeney, 1980;Amiel et al, 1982;Noyes et al, 1984;Shino et al, 1984;Nikolaou et al, 1986;Jackson et al, 1987), nutrition (Whiteside and Sweeney, 1980;Amiel et al, 1986a;Skyhar et al, 1985), and fibroblast re-population (Kennedy et al, 1976;Clancy et al, 1981;Arnoczky et al, 1982;Amiel et al, 1984Amiel et al, , 1986cKleiner et al, 1986;Nikolaou et al, 1986;van Rens et al, 1986;Jackson et al, 1987;Clark and Sidles, 1990;Christel and Gibbons, 1993;Petersen et al, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…22 In addition, many of these studies found that cells in the transplanted ligaments repopulated not by the multiplication of donor cells, but by the introduction of recipient cells into the graft site. 11 If these observations are a true reflection of the natural course of cellular events in the reconstitution of a transplanted ligament, then the viability of donor cells is less important than has been previously thought.…”
Section: Discussionmentioning
confidence: 99%